High concentration of black carbon in northern Pakistan: Characteristics, source apportionment and emission source regions. (15th January 2023) - ul Haq, Ehtiram; Alam, Khan; Bibi, Samina; Roy, Arindam
Abstract: Atmospheric Black Carbon (BC) is one of the absorbing components of solar radiation which potentially affects human health and regional climate. In the current study, BC mass concentrations were regularly observed for pre-monsoon and monsoon seasons using the seven-channel aethalometer (AE-33) over Peshawar, Pakistan. The scarcity of BC measurement in this region is critical for air quality assessment, hence providing much importance to this article for control policy recommendations. The monthly mean BC showed a maximum value of 12.1 ± 5.4 μg/m 3 during March and a minimum value of 6.4 ± 3.1 μg/m 3 during July. The bimodal diurnal BC concentration was observed in between 05:00–08:00 and 20:00–24:00 LST having a maximum night/day ratio of 3.4 during April. Furthermore, the weekdays BC concentration was higher than weekend days having the highest weekdays concentration during March (12.9 ± 5.6 μg/m 3 ) and the lowest concentration during July (6.9 ±0 .9 μg/m 3 ). Moreover, BC contributed maximum of 22% to PM2.5 during April and minimum of 7% during June. The source apportionment of BC revealed that maximum value of BC emitted from fossil fuel (BCFF ) and biomass burning (BCBB ) were 9.90 ± 0.50 μg/m 3 and 2.61 ± 0.49 μg/m 3 during March showed a clear dominancy of BCFF over BCBB emission. Further the highest percentage contribution of BCFF and BCBB were found to be 80.45% and 22.27% to total BC during May and April, respectively. Finally, the cluster trajectory analysis showed that majority of the air pollutants were due to local emission rather than long range transport. Graphical abstract: Image 1 Highlights: Detailed temporal analysis of BC, BCFF and BCBB were carried out. Dominant BC concentration were observed in pre-monsoon season than monsoon season. Fossil fuel emission was about 3 times higher than biomass burning. Major potential sources of BC were originated from local as well as neighbor regions.